The Role of Empathy and Life Satisfaction in Internet and Smartphone Use Disorder - Lachmann, Bernd; Sindermann, Cornelia; Sariyska, Rayna Y.; Luo, Ruixue; Melchers, Martin C.; Becker, Benjamin; Cooper, Andrew J.; Montag, Christian (Frontiers in Psychology, 2018)
Recent studies have yielded initial evidence for an association between Internet Use Disorder (IUD), empathy, and life satisfaction. In the present study we sought to replicate these previous findings, and then to extend this research by also examining the relationship between empathy, life satisfaction, and the related phenomenon of Smartphone Use Disorder (SUD). The present study included independent samples from China (N = 612, 162 females) and Germany (N = 304, 207 females), with the same set of questionnaires administered to both samples. IUD was measured with Pawlikowski’s s-IAT and SUD was assessed with the short version of Kwon’s Smartphone Addiction Scale. The Interpersonal Reactivity Index (IRI) was used to assess individual differences in empathy. Please note that for the German sample also data on the empathy quotient (EQ) are available. Life satisfaction data was collected using items from the SOEP-Questionnaire (Socio-Economic Panel, Germany)In both of our samples we replicated previous findings showing the association between higher IUD, lower empathy, and lower life satisfaction scores. In addition, individuals with higher SUD showed higher scores on the IRI Personal Distress scale in China and Germany, while further associations between IRI dimensions and SUD were only found in the Chinese sample. Personal Distress is known to be highly correlated with the personality trait of Neuroticism, hence higher stress/negative emotionality in tense social situations is related to SUD. In the present study we confirm earlier findings showing the relationship between empathy, life satisfaction, and IUD, and extend some of these findings to SUD. We also emphasize the importance of cross-cultural studies when investigating IUD/SUD in the context of empathy and life satisfaction.